Synthesis of Phenothiazine Derivatives and their Diverse Biological Activities: A Review - Kaur, Prabhjot; Utreja, Divya; Sharma, Shivali (Mini Reviews in Medicinal Chemistry, 2025)
The increasing resistance of causative agents to current treatments has made infectious disease management more challenging. Heterocyclic compounds have garnered considerable attention due to their numerous significant medical and biological applications. Research interest in heterocyclic compounds is rapidly increasing due to extensive synthetic studies and their functional utility. Phenothiazine (PTZ), an organic thiazine compound, has a broad range of biological activities, including antimicrobial, antimalarial, antipsychotic, anti-inflammatory, and antiemetic effects. Additionally, modifications to the phenothiazine structure have enhanced its efficacy, making it a potential candidate for addressing drug-resistant infections. This review examines recent synthesis methods, including catalytic and microwave-assisted techniques, which have expanded the applications of phenothiazine derivatives. The article also discusses structure-activity relationships, which help optimize the pharmacological properties of these compounds for future therapeutic use.
Keywords: phenothiazine